Malignant mesothelioma - Tannapfel, Andrea (Recent results in cancer research, 2011)
Malignant mesothelioma is an aggressive and fatal neoplasm of serous membranes. The pathogenesis of malignant mesothelioma is clearly linked to incorporated asbestos fibers. Owing to the late banning of asbestos use in industrial nations and the continuing mining and consumption of asbestos in many countries, the incidence of malignant mesothelioma is still rising worldwide. This book covers all the important aspects of the disease by bringing together contributions from selected experts in the fields of epidemiology, imaging, pathological diagnosis, therapy, genetics, and screening. Special emphasis is placed on the latest diagnostic techniques and current therapy standards. In addition, the mineralogy of asbestos is reviewed and clear advice is included on the analysis of tissue mineral fiber content. By providing a compact, scientifically based, and up-to-date overview of the management of malignant mesothelioma, this volume will be invaluable for all clinicians and pathologists who are engaged in the diagnosis and treatment of the disease or in related research.